Implementasi Model Pembelajaran Two Stay Two Stray untuk memperbaiki Komunikasi Matematika Siswa Kelas XII XII-2 SMAN Model Terpadu Madani - Razi, Muhammad Fahrur; Sasongko, Luddy Bambang; Lefrida, Rita (Postulat : Jurnal Inovasi Pendidikan Matematika, 2023)
In learning students convey the results of their work is not always easy to accept. This is because their level of mathematical communication is not high. To improve their communication skills, a learning model that emphasizes communication aspects is needed, one of these models is two stay two stray. For this reason, through this study to improve students' mathematical communication skills, the two stay two stray learning model was applied to the limit material of trigonometric functions. This research was conducted on students of class XII-2 of Madani Integrated Model Senior High School in the 2022/2023 school year. This research is a collaborative classroom action research (PTK) which is carried out in 2 learning cycles. The results of the research in cycle 1 get the level of mathematical communication skills of student A is at level 1, student B is at level 2, student C is at level 3. Then revisions were made in cycle 2 learning to get the results of student A at level 2, student B at level 3 and student C at Level 3. From these results it can be concluded that learning mathematics by applying the two stay two stray type cooperative learning model can improve mathematical communication skills for students who have low and medium abilities.Keywords : Two stay two stray, Mathematical Communication